2021
DOI: 10.1136/bcr-2020-240379
|View full text |Cite
|
Sign up to set email alerts
|

Double inferior vena cava in a monochorionic twin pregnancy with selective fetal growth restriction

Abstract: Congenital anomalies of the infrarenal inferior vena cava (IVC) are well described in adult life, however, little information exists on their associations in fetal life. Here, we describe a case of a monochorionic diamniotic (MCDA) twin pregnancy complicated by selective fetal growth restriction (sFGR) with an incidental finding of a double IVC in one child. In fetal life, variants of the infrarenal IVC are strongly associated with heart defects, which might suggest haemodynamic alterations or genetic causes, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Bilateral caval veins and PLSVC malformations are rare abnormal body veins in fetuses. [6][7][8] PLSVC is a relatively common malformation, with an incidence rate of 4.0% in congenital heart disease. The common cardiac malformations include isomerism, atrioventricular septal defect, and left ventricular outflow tract obstruction, elt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral caval veins and PLSVC malformations are rare abnormal body veins in fetuses. [6][7][8] PLSVC is a relatively common malformation, with an incidence rate of 4.0% in congenital heart disease. The common cardiac malformations include isomerism, atrioventricular septal defect, and left ventricular outflow tract obstruction, elt.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral caval veins and PLSVC malformations are rare abnormal body veins in fetuses 6–8 . PLSVC is a relatively common malformation, with an incidence rate of 4.0% in congenital heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Bakry et al 9 reported prenatally diagnosed double IVC with interruption of the suprarenal part with azygous continuation. Mosimann et al 14 described a IVC duplication in one fetus in a monochorionic diamniotic twins. Zhang et al reported on series of prenatally diagnosed cases of left IVC and double IVC and showed high rate of associated anomalies, mostly cardiac.…”
Section: Orcidmentioning
confidence: 99%